If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 2 = 7(x + -2) + 4 Reorder the terms: 2 + 8x = 7(x + -2) + 4 Reorder the terms: 2 + 8x = 7(-2 + x) + 4 2 + 8x = (-2 * 7 + x * 7) + 4 2 + 8x = (-14 + 7x) + 4 Reorder the terms: 2 + 8x = -14 + 4 + 7x Combine like terms: -14 + 4 = -10 2 + 8x = -10 + 7x Solving 2 + 8x = -10 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 2 + 8x + -7x = -10 + 7x + -7x Combine like terms: 8x + -7x = 1x 2 + 1x = -10 + 7x + -7x Combine like terms: 7x + -7x = 0 2 + 1x = -10 + 0 2 + 1x = -10 Add '-2' to each side of the equation. 2 + -2 + 1x = -10 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = -10 + -2 1x = -10 + -2 Combine like terms: -10 + -2 = -12 1x = -12 Divide each side by '1'. x = -12 Simplifying x = -12
| 15x-12y=141 | | 8+40n-35=-307 | | 4x+72=3x+36 | | 2P=q+5 | | -7+4y-2y+4=0 | | 10=a(43)(3) | | 16+11h=7+9+11h | | -11+13v-19v=3-8v | | -20+7t=-13+7t+2 | | x^2+7x-5= | | 0.5x+x=4.75 | | 5x+118+3x+126= | | 10k-5=-3+10k-2 | | -1/2k=3/4k-3 | | 5.8=-logarithm(Ka) | | -7+6n=7+6n | | -15-9+13p=-13+14p | | y=kx+5 | | F(x)=15x-8 | | 5(5x-4)+11=-3 | | 7-3m=40 | | c+14c+11=7c-13 | | -2(0)+1=5-2(0) | | 2m-8=19-m | | 2(3d+c)-(4d+2c)= | | -2f=2+1-2f | | 7-3(m)=40 | | -3w+3=3-3w | | f(y)=x^2+3.6x-0.7 | | -6r-1=-2-6r | | -7q-10=-4q+8 | | 3s-10=-10+3s |